Bilateral Mammary Tuberculosis Associated with a Borderline Ovarian Tumor - Van Keirsbilck, Joachim (S. Karger GmbH, 2008)
BACKGROUND: Mammary tuberculosis is rare in the Western world. It has no defined clinical or imaging features, and has to be differentiated from breast cancer and an abscess. CASE REPORT: We present a case of mammary tuberculosis combined with borderline ovarian cancer. The bilateral breast tuberculosis was the first and only symptom of underlying tuberculosis with Ziehl-Neelsen-positive para-aortic lymph nodes. During further exploration, an asymptomatic pelvic mass was discovered, which appeared later to be a borderline ovarian tumor. The patient was treated with tuberculostatic therapy for 6 months, resulting in a complete regression of the breast lesions. She also underwent hysterectomy with bilateral salpingo-oophorectomy and lymph node dissection for her ovarian cancer. CONCLUSIONS: This case report emphasizes that breast tuberculosis should be included in the differential diagnosis of any atypical breast mass.